Pengaruh Kinerja Keuangan dan Kinerja Sosial Terhadap Kepercayaan Masyarakat Pada Bank Pembiayaan Rakyat Syariah - Sari, Eka Septia; Indrarini, Rachma (Universitas Negeri Surabaya, 2019)
The research aims to test the effect of financial performance and social performance towards public trust of Bank Pembiayaan Rakyat Syariah (BPRS). The research methods used in this research is quantitative with an associative approach. Number of samples that used is 10 of Bank Pembiayaan Rakyat Syariah (BPRS) through purposive sampling technique. This research used secondary data that is financial statements 2015-2017 period. The result of this research shows that financial performance and social performance simultaneously has significant effect to public trust. Meanwhile, based on partial test shows that financial performance has no significant effect to public trust and social performance has significant effect to public trust.